Strong hole-photon coupling in planar Ge for probing charge degree and strongly correlated states - Franco De Palma; Fabian Oppliger; Wonjin Jang; Stefano Bosco; Marián Janík; Stefano Calcaterra; Georgios Katsaros; Giovanni Isella; Daniel Loss; Pasquale Scarlino (Nature Communications)
Abstract Semiconductor quantum dots (QDs) in planar germanium (Ge) heterostructures have emerged as front-runners for future hole-based quantum processors. Here, we present strong coupling between a hole charge qubit, defined in a double quantum dot (DQD) in planar Ge, and microwave photons in a high-impedance (Z r = 1.3 kΩ) resonator based on an array of superconducting quantum interference devices (SQUIDs). Our investigation reveals vacuum-Rabi splittings with coupling strengths up to g 0/2π = 260 MHz, and a cooperativity of C ~ 100, dependent on DQD tuning. Furthermore, utilizing the frequency tunability of our resonator, we explore the quenched energy splitting associated with strong Coulomb correlation effects in Ge QDs. The observed enhanced coherence of the strongly correlated excited state signals the presence of distinct symmetries within related spin functions, serving as a precursor to the strong coupling between photons and spin-charge hybrid qubits in planar Ge. This work paves the way towards coherent quantum connections between remote hole qubits in planar Ge, required to scale up hole-based quantum processors.